Exercise training for improving outcomes post-burns: a systematic review and meta-analysis. (June 2018) - Flores, Orlando; Tyack, Zephanie; Stockton, Kellie; Ware, Robert; Paratz, Jennifer D
Objectives: To determine the effectiveness of different modalities of exercise and to evaluate the safety of exercise-based interventions post-burns. Data sources: Six databases were searched from inception to October 2017 using "burn, " "exercise" and synonyms as keywords. Relevant authors, key journals and reference lists of included studies were hand-searched. Review methods: Articles reporting on exercise interventions in patients post-burn and considering physical, physiological or psychological outcomes were considered. Two authors independently screened 2253 records and selected 19 articles for inclusion. The quality of the evidence was assessed at the study level and at the outcome level. Results: Unbiased effect size estimators (pooled Hedges' g ) with 95% confidence intervals (CIs) were calculated if there were two or more trials with homogeneous outcomes. There were no significant differences post-exercise training in VO2peak ( g  = 0.99; 95% CI: −0.4 to 2.4: P  = 0.18), resting energy expenditure ( g  = −0.51; 95% CI: −1.99 to 0.97: P  = 0.5) and muscle strength ( g  = 0.51; 95% CI: −0.03 to 1.05: P  = 0.07) between groups. Evidence suggested exercise had a beneficial effect on body composition ( g  = 0.59; 95% CI: 0.05 to 1.14: P  = 0.03), need of surgical release of contractures (risk ratio = 0.34; 95% CI: 0.2 to 0.7; P  = 0.004) and health-related quality of life. However, a lack of evidence existed regarding the safety of exercise training post-burns. Conclusion: Limited evidence suggests that exercise has a beneficial effect on physical and physiological outcomes in patients post-burn. Further trials using high-quality methodology are required, with focus on reporting of adverse events, health-related quality of life and psychological outcomes.